A polynomial $p(x)$ with real coefficients is of degree five. The equation $p(x)=0$ has a complex root $2+i$. The graph $y=p(x)$ has the x-axis as a tangent at $(2,0)$ and intersects the cordinate axes at $(-1,0)$ and $(0,4)$. Find $p(x)$ in factorised form with real coefficients.

Firts I found the roots:

$r_1=2+i$, $r_2=2-i$, $r_3=-1$, $r_4=2$ and $r_5=a$, I was not able to find it ( for some reason the anwser considered $r_5=2$, but I was not able to prove it)







Observation: if we consider the value of $a=2$ then the answer is right. However I cannot show that $a=2$

  • 3
    $\begingroup$ The graph of $p(x)$ has the $x$-axis as a tangent at $(0,2)$. Tangent means multiple root! $\endgroup$
    – Qurultay
    Apr 2 '18 at 13:12
  • 1
    $\begingroup$ You must use that $$p'(0)=2$$ $\endgroup$ Apr 2 '18 at 13:14
  • $\begingroup$ @Dr.SonnhardGraubner You must have meant $p'(2) = 0$. $\endgroup$
    – Deepak
    Apr 2 '18 at 14:08
  • $\begingroup$ Sorry, yes that is what i meant! $\endgroup$ Apr 2 '18 at 14:09
  • $\begingroup$ @Qurultay .& that's all there is to it, as we also have p(0)=4. $\endgroup$ Apr 2 '18 at 14:38

Let $f(x)=g(x)(x-2)(x-a)$, where $g(x)=B(x+1)(x-2+i)(x-2-i)$. The $x$ axis has slope $0$. Since $f$ is tangent to the $x$ axis at $x=2$, we have

$$f'(2)=0$$ But $$f'(x)=g'(x)(x-2)(x-a)+g(x)(x-a)+g(x)(x-2)$$ so that $$f'(2)=g(2)(2-a)=0$$ Since $g(2)\ne 0$, we must have $a=2$


As the excellent hint in the comment stated, an $x$-axis tangent means a repeated root. That means that $(x-2)$ is a repeated factor of $p(x)$, i.e that $(x-1)^m, m \geq 2$ is a factor of $p(x)$.

The other obvious factors are $(x+1)$ and $(x-(2+i))(x-(2-i)) = (x^2 - 4x + 5)$, which, when multiplied together, gives you a cubic.

That means that the only remaining factor to achieve a fifth degree polynomial is of degree two, and therefore it must be $(x-2)^2$.

So $p(x) = k(x-2)^2(x+1)(x^2-4x+5)$

Apply the last piece of information, that $p(0) = 4$, which gives $k(4)(1)(5) = 4$ or $k = \frac 15$, so $p(x) = \frac 15(x-2)^2(x+1)(x^2-4x+5)$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.